Procedural justice judgments and organizational citizenship behavior: examining the role of commitment as a mediator / Aizzat Mohd. Nasurdin and T. Ramayah (Faculty of Business and Management ; UiTM Press, 2006)
The purpose of this paper is to determine the influence of procedural justice on two forms of organizational citizenship behavior (interpersonally-focused OCBI and organizationally-focused OCBO) and whether organizational commitment plays a role in mediating the above-mentioned relationships. Based on the social exchange framework (Blau, 1964), the norm of reciprocity (Gouldner, 1960), and the "group-value" model (Lind & Tyler, 1988), a study was conducted among hotel employees in Malaysia. Regression analyses on a sample of 188 respondents revealed that procedural justice had a significant and positive effect on both OCBI and OCBO. Specifically, the effect of procedural justice was stronger on OCBI than OCBO. The hypothesis concerning the role of commitment as a mediator, however, was not supported.